Implikasi Pembelajaran Ahlusunnah Wal Jama’ah Terhadap Penguatan Moderasi Beragama - Moch Zainal Arifin Hasan; Muhammad Rizal Ansori (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The research aims to understand the alignment and the impact resulting from the study and deepening of Aswaja on the development of religious moderation. The method used is qualitative with a qualitative descriptive approach. The research findings reveal that Aswaja has four principles to adhere to: tawasuth, tawazun, tasamuh, and tawazun. Meanwhile, religious moderation encompasses nine principles: humanity, public welfare, justice, balance, constitutional compliance, national commitment, tolerance, anti-violence, and respect for traditions. The implications of studying Aswaja for religious moderation are significant. Tawasuth fosters inclusivity, dialogue, and a deep understanding of religion. Tawazun emphasizes balance, prevents extremism, and promotes tolerance. Tasamuh supports the acceptance of differences, rejects radicalism, and creates harmony. I'tidal enables a profound understanding of religion and the preservation of justice. Aswaja education prioritizes attitudes that empower individuals to actively contribute to building an inclusive, tolerant, and just society, in line with moderate religious principles. As a result, these attitudes have a significant positive impact on the development of religious moderation.